Operculina turpethum (Linn.) Silva Manso as a Medicinal Plant Species: A Review on Bioactive Components and Pharmacological Properties - Gupta, Shweta; Ved, Akash (Pharmacognosy Reviews)
Operculina turpethum (Linn.) (OT) Silva Manso belongs to the family Convolvulaceae. This review incorporates literature for the phytochemical and pharmacological profile of OT herb. Exhaustive literature survey was done using all the details on phytochemistry and pharmacology of OT available. This herb was found to be a potent source of bioactive compounds such as α‑ and β‑turpethein, turpethinic acids (A, B, C, D, and E), coumarins, cycloartenol, lanosta‑5‑ene, 24‑methylene‑δ‑5‑lanosterol, α‑ and β‑rhamnose, β‑sitosterol, lupeol, scopoletin, betulin, acrylamide, stigma‑5,22dien‑3‑O‑β‑D‑glucopyr anoside, β‑sitosterol‑β‑D‑glucoside (H‑1), 22,23‑dihydro‑α‑spinosterol‑β‑D‑glucoside (H‑2), and salicylic acid (CH‑2), which are useful in fevers, edema, ascites, anorexia, constipation, hepatosplenomegaly, hemorrhoids, cervical lymphadenitis, fistulas, constipation, chronic gout, fever, bronchitis, ulcers, hemorrhoids, tumors, obesity, jaundice, herpes, induce lacrimation, and other skin disorders. From the aerial parts of OT, four new dammarane‑type saponins that are operculinosides A–D (1–4) were isolated that showed particular hepatoprotective activities. All the compounds are reported to possess pharmacological properties such as antibacterial, anti‑inflammatory, analgesic, hepatoprotective, anti‑arthritic, ulcer protective, antidiarrheal, antidiabetic, and cytotoxic properties.
Keywords: Convolvulaceae; Operculina turpethum; operculinosides; turpethinic acids